2012
DOI: 10.4021/jmc807w
|View full text |Cite
|
Sign up to set email alerts
|

Potential Linagliptin-Induced Renal Impairment

Abstract: It is known that linagliptin, a novel DPP-4 inhibitor, can be used in patients even with severe renal impairment. So far, there have been no reports describing the clinical presentations and features of a patient with linagliptin-induced renal toxicity. A 66-year-old Japanese man had developed nausea and elevations of creatinine and potassium levels at 4 weeks after switching from sitagliptin to linagliptin. No emesis or diarrhea was noted. These renal parameters had slowly recovered after switching-back to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Although there have been isolated case reports of renal toxicity after initiation of DPP‐4 inhibitors , an increased risk has not been confirmed in large managed care and pooled trial database analyses of people given appropriate recommended doses . In addition, there is no clear safety signal from the long‐term efficacy studies in people with renal impairment as summarized in Table , but also from the Saxagliptin Assessment of Vascular Outcomes Recorded in Patients with Diabetes Mellitus (SAVOR TIMI 53) and Examination of Cardiovascular Outcomes with Alogliptin versus Standard of Care (EXAMINE) trials, the two recently reported large‐scale cardiovascular safety studies of DPP‐4 inhibitor therapy that both included significant proportions of people with renal impairment [16% with estimated glomerular filtration rate (eGFR) ≤50 ml/min/1.73 m 2 in SAVOR TIMI 53, and 29% with eGFR <60 ml/min/1.73 m 2 in EXAMINE].…”
Section: Tolerability and Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been isolated case reports of renal toxicity after initiation of DPP‐4 inhibitors , an increased risk has not been confirmed in large managed care and pooled trial database analyses of people given appropriate recommended doses . In addition, there is no clear safety signal from the long‐term efficacy studies in people with renal impairment as summarized in Table , but also from the Saxagliptin Assessment of Vascular Outcomes Recorded in Patients with Diabetes Mellitus (SAVOR TIMI 53) and Examination of Cardiovascular Outcomes with Alogliptin versus Standard of Care (EXAMINE) trials, the two recently reported large‐scale cardiovascular safety studies of DPP‐4 inhibitor therapy that both included significant proportions of people with renal impairment [16% with estimated glomerular filtration rate (eGFR) ≤50 ml/min/1.73 m 2 in SAVOR TIMI 53, and 29% with eGFR <60 ml/min/1.73 m 2 in EXAMINE].…”
Section: Tolerability and Safetymentioning
confidence: 99%
“…Although there have been isolated case reports of renal toxicity after initiation of DPP-4 inhibitors [40][41][42], an increased risk has not been confirmed in large managed care and pooled trial database analyses of people given appropriate recommended doses [43,44]. In addition, there is no clear safety signal from the long-term efficacy studies in people with renal impairment as summarized in Table 3 In SAVOR TIMI 53, people were excluded if they had ESRD and were undergoing long-term dialysis, had undergone a renal transplantation or had a serum creatinine >530 μmol/l [4].…”
Section: Renal Toxicitymentioning
confidence: 99%
“…Moreover, our study classified the data in more detail by stratification according to age and sex. Some case reports have suggested that linagliptin can cause acute renal failure with hypotension and hyperkalemia when added to the treatment regimens of patients already receiving ACEIs 30,31 . Moreover, a recent in silico and in vivo study reported that many DPP-4Is, including linagliptin, could potentially inhibit ACE in concentrations close to those required for DPP-4 inhibition 32 .…”
Section: Discussionmentioning
confidence: 99%
“…It may be prudent to exert caution when linagliptin is initiated in combination with ACE-inhibitors in patients with limited kidney reserve. Of note, a case of transient AKI associated with linagliptin use was reported in a patient with normal renal function who was also on ACE-inhibitor [ 7 ]. Therefore, we recommend to closely monitoring kidney function and blood pressure after linagliptin initiation in diabetic patients with advanced CKD also treated with ACE-inhibitors.…”
Section: Discussionmentioning
confidence: 99%